REPRESENTASI IDENTITAS ETNIS MELALUI BAHASA DALAM FILM SERI “ARAB MAKLUM” - Syaifullah, Syaifullah; Adila, Wildi; Setyawan, Cahya Edi (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
This study describes the role of language in presenting culture and ethnic identity through the medium of the film series